Collagen Nanoparticle-Mediated Brain Silymarin Delivery: An Approach for Treating Cerebral Ischemia and Reperfusion-Induced Brain Injury - Rathore, Pankaj; Arora, Indu; Rastogi, Shweta; Akhtar, Mohd; Singh, Shruti; Samim, Mohammed (Frontiers in Neuroscience, 2020)
Silymarinis a bioactive constituent isolated from milk thistle (Silybummarinum). Since its discovery silymarin has been considered a gold standard drug in treating ailments related to liver, resulting out of alcohol consumption and viral hepatitis. This hepatoprotective nature of silymarinarises out of anti-oxidative and tissue regenerating properties of silymarin. But several recent studies have established the neuroprotective link of silymarin also.Thus, the present study was designed to explore the neuroprotective aspect of nanosilymarin (silymarin encapsulated inside collagen based polymeric nanoparticulate drug delivery system). This study aimed at bringing out the role of nanoparticlesin enhancing the therapeutic effect of silymarin against neuronal injury, originating from middle cerebral artery (MCAO) induced oxidative stress related brain damages in focal cerebral ischemia.Collagen based micellar nanoparticles were prepared and stabilized using 3- ethylcarbodiimide-hydrochloride (EDC-Hcl) and malondialdehyde (MDA) as cross linkers. Nanoparticles were characterized using Dynamic light scattering(DLS), Transmission electron microscopy(TEM) and Fourier transform infrared spectroscopy(FT-IR) techniques and the size of nanoparticles was found to be around 48 nm.Male albino wistar rats were pretreated with three different doses of nanosilymarinof 10µg, 100µg and 1000µg/kg b.wtand a dose of free silymarin of 100 mg/kg b.wtintraperitoneally (i.p.) for 7 days. Focal cerebral ischemia was induced using MCAO model on the 8th day for 1 h followed by 24 h of reperfusion. The animals were then evaluated for neurobehavioral,infarct analysis,biochemical, histopathological andimmunohistochemical studies. All the above parameters showed remarkable improvement in nanosilymarin treated groups in comparison tosilymarin treated group.Nanoparticle encapsulation of drug enhanced neuroprotection by increasing drug bioavailability and targeting. Thus, the present study concluded with satisfactory results, showing the critical role played by nanoparticles in improving the neuroprotection with very low drug doses.